2017
DOI: 10.1093/nar/gkx518
|View full text |Cite
|
Sign up to set email alerts
|

Strand-specific CpG hemimethylation, a novel epigenetic modification functional for genomic imprinting

Abstract: Imprinted genes are regulated by allele-specific differentially DNA-methylated regions (DMRs). Epigenetic methylation of the CpGs constituting these DMRs is established in the germline, resulting in a 5-methylcytosine-specific pattern that is tightly maintained in somatic tissues. Here, we show a novel epigenetic mark, characterized by strand-specific hemimethylation of contiguous CpG sites affecting the germline DMR of the murine Peg3, but not Snrpn, imprinted domain. This modification is enriched in tetraplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…S4C). Notably, the imprinting region of GNAS also exhibited hemimethylation, which is in line with recent studies on imprinting regions (Guntrum et al 2017;Patino-Parrado et al 2017). The stable hemimethylation at individual CpGs of senescence-associated regions and on specific DNA strands argues against the possibility that this effect is caused by loss of DNAm during cell divisionit might rather be evoked by altered states of higher order chromatin conformation (Xu and Corces 2018).…”
Section: Senescence-associated Dna Methylation Is Often Strand-specificsupporting
confidence: 90%
See 1 more Smart Citation
“…S4C). Notably, the imprinting region of GNAS also exhibited hemimethylation, which is in line with recent studies on imprinting regions (Guntrum et al 2017;Patino-Parrado et al 2017). The stable hemimethylation at individual CpGs of senescence-associated regions and on specific DNA strands argues against the possibility that this effect is caused by loss of DNAm during cell divisionit might rather be evoked by altered states of higher order chromatin conformation (Xu and Corces 2018).…”
Section: Senescence-associated Dna Methylation Is Often Strand-specificsupporting
confidence: 90%
“…DNAm maintenance is particularly mediated by DNA methyltransferase 1 (DNMT1) but also by the de novo methyltransferases DNMT3A and DNMT3B (Jones and Liang 2009). Using hairpinbisulfite PCR (Laird et al 2004) several studies have demonstrated that, despite the general preference for concordant DNA methylation on both strands, some particular sites are specifically methylated on only one strand (Arand et al 2015;Choi et al 2017;Patino-Parrado et al 2017). More recently, it was shown that such hemimethylation is stably inherited over several passages and that hemimethylated sites are associated with CCCTC-binding factor (CTCF)/cohesin binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hemimethylation may serve as a stable epigenetic mark. In addition, recent papers show that hemimethylation is a characteristic of secondary differential methylation regions that are associated with imprinted genes [ 54 56 ]. That is, hemimethylation is a novel epigenetic modification functional for genomic imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, pyrosequencing was selected as it is the standard technique in cancer research, detects small differences in methylation, is suitable for heterogeneous samples and provides quantitative results ( 67 , 68 ). However, it was not possible to determine whether it provides information on allele specificity or hemi-methylation, which may differentiate de novo methylation events from maintenance factors ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%